2008
DOI: 10.1038/nm.1879
|View full text |Cite
|
Sign up to set email alerts
|

Modification of mineralocorticoid receptor function by Rac1 GTPase: implication in proteinuric kidney disease

Abstract: Blockade of mineralocorticoid receptor has been shown to improve the clinical outcomes of proteinuric kidney diseases. However, little is known about the regulation of mineralocorticoid receptor-dependent transcriptional activity in renal disease. Here we identify a new role for Rac1, a member of the Rho family GTPases, as a potent activator of mineralocorticoid receptor signal transduction both in vitro and in vivo. Transient transfection assays in HEK 293 cells revealed that constitutively active Rac1 (CA-Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
382
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(406 citation statements)
references
References 34 publications
19
382
2
3
Order By: Relevance
“…Administration of an anti-CF6 antibody at 113 ÎŒg/kg for three consecutive days to transgenic mice improved the salt-induced hypertension. Since RAC1, a member of the Rho family GTPases, was recently identified as a determinant molecule for salt-sensitive hypertension via activation of mineralocorticoid receptor [22], we measured RAC1 activity in the kidney of transgenic mice. Pull-down assays revealed that transgenic mice had more active GTPases than control wild-type mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of an anti-CF6 antibody at 113 ÎŒg/kg for three consecutive days to transgenic mice improved the salt-induced hypertension. Since RAC1, a member of the Rho family GTPases, was recently identified as a determinant molecule for salt-sensitive hypertension via activation of mineralocorticoid receptor [22], we measured RAC1 activity in the kidney of transgenic mice. Pull-down assays revealed that transgenic mice had more active GTPases than control wild-type mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A high-salt diet increased systolic and diastolic blood pressure in transgenic mice, and this salt-induced hypertension was improved by administration of an anti-CF6 antibody. Since RAC1 was recently identified as a determinant molecule for salt-sensitive hypertension via activation of mineralocorticoid receptor [22], we investigated a possible involvement of RAC1 activation in the genesis of salt-sensitive hypertension in transgenic mice. Pull-down assays clearly showed that transgenic mice had more active GTPases in the kidney than wild-type mice, while RAC1-GTP was increased by extracellular acidosis and amiloride administration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MRs were activated by Rac1, which was independent of aldosterone in the kidney. 43 Further studies are needed to clarify the precise mechanisms involved in the activation of MR in the RVLM.…”
Section: Discussionmentioning
confidence: 99%
“…They have identified a new role for Rac1, a member of the Rho family of GTPases, as a potent activator of MR signal transduction both in vitro and in vivo. 26 The constitutively active Rac1 enhances nuclear translocation and the transcriptional activity of MR in vitro. They showed that a unique Rac-specific inhibitor, NSC23766, effectively ameliorates proteinuria and glomerular damage in the DS rats.…”
Section: Effects Of Eplerenone In Experimental Animal Models With Salmentioning
confidence: 99%